Antibiotic-Resistant Bacteria: Dairy Industry Represents a Source of Bacterial Contamination to Groundwater - Iqbal, Muhammad Naeem; Ashraf, Asfa (PSM Biological Research, 2023)
The dairy industry is producing unsustainable amounts of untreated manure that seeps into the groundwater, threatening the livelihood of millions of people, eradicating entire ecosystems. Dairy farms have the potential to contaminate the groundwater. The dairy industry also causes damage through the huge quantities of antibiotics, pesticides and insecticides. Bacteria are abundant in the faeces that dairy farms release into water sources. These bacteria naturally harm other organisms and develop resistance to multiple antibiotics, disrupt the natural ecology in addition to making water dangerous for people. In this issue, Bello and Echevarría (2023) documented several antibiotic resistant bacteria in groundwater near dairy farms. People can be exposed to waterborne pathogenic microbes by consuming contaminated water or by using contaminated water for food production and/or processing. Proper manure handling can reduce the risk of groundwater contamination in the vicinity of dairy farms.